Gender differences in patients with venous thromboembolism and five common sites of cancer. Issue 151 (March 2017) - Martín-Martos, Francisco; Trujillo-Santos, Javier; del Toro, Jorge; Bura-Riviere, Alessandra; Lorenzo, Alicia; Barillari, Giovanni; Soler, Silvia; Mahè, Isabelle; Sahuquillo, Joan Carles; Monreal, Manuel
ABSTRACT: Background: The outcome of cancer patients with venous thromboembolism (VTE) may differ according to gender. Methods: We used the RIETE database to compare the rate of VTE recurrences, major bleeding and mortality in patients with lung, colorectal, pancreatic, hematologic or gastric cancer during the course of anticoagulation, according to gender. Results: As of January 2016, 11, 055 patients with active cancer were enrolled: 1, 727 had lung cancer, 1, 592 colorectal, 840 hematologic, 517 pancreatic and 459 had gastric cancer. Compared with men ( N = 3, 130), women ( N = 2, 005) were more likely to have colorectal, pancreatic or hematologic cancer, and less likely to have lung cancer. Most patients (91%) were initially treated with low-molecular-weight heparin (LMWH), but women received higher daily doses per body weight. Then, 66% kept receiving LMWH for long-term therapy. During the course of anticoagulation, 302 patients developed recurrent VTE, 220 bled and 1, 749 died. Compared with men, women had a similar rate of VTE recurrences or major bleeding, and a lower mortality (risk ratio [RR]: 0.90; 95% CI: 0.82–0.99). When separately comparing outcomes according to cancer site, women with lung cancer had a lower mortality (RR: 0.79; 95% CI: 0.70–0.92), those with colorectal cancer had a higher mortality (RR: 1.25; 95% CI: 1.02–1.54) and those with gastric cancer had a higher rate of VTE recurrences than men (RR: 2.47; 95% CI: 1.04–5.89). Conclusions: VTE women with lung, colorectal, pancreatic, haematological or gastric cancer experienced a similar outcome during the course of anticoagulant therapy than men with similar cancers.